Pentecostalism and Witchcraft: Spiritual Warfare in Africa and Melanesia - Knut Rio (Contemporary Anthropology of Religion, 2017)
This open access book presents fresh ethnographic work from the regions of Africa and Melanesia-where the popularity of charismatic Christianity can be linked to a revival and transformation of witchcraft. The volume demonstrates how the Holy Spirit has become an adversary to the reconfirmed presence of witches, demons, and sorcerers as manifestations of evil. We learn how this is articulated in spiritual warfare, in crusades, and in healing or witch-killing raids. The contributors highlight what happens to phenomena that people address as locally specific witchcraft or sorcery when re-molded within the universalist Pentecostal demonology, vocabulary, and confrontational methodology.